Use of differents potato somaclons for evaluating the resistance to Alternaria solani Sorauer by artificial inoculation in field condition - Michel Leiva-Mora; Novisel Veitía; Miguel Angel Dita Rodríguez (Biotecnología Vegetal, 2001)
The use of plant pathogens, for the genetic improving programs is an important matter to guarantee its success. Utilization of phytopathogenic isolates from natural source, let us to employ rapid screening in some important genotypes. In this work it was used a mycelium homogenizated of Alternaria solani Sor (strain IBP-As-4), with a relative concentration of 1.7x105 ufc ml-1. The inoculum was applied by spraying to the somaclons (obtained by mutagenic and in vitro selection with culture filtrated of the fungus), also to the susceptible (Desireé) and resistant (Solanum chacoense) cultivars, respectively. The first symptoms appeared after seventh day of inoculation. The behavior between somaclons and testers in the final evaluation were different. Solanum chacoense was the most resistant genotype, the somaclons IBP-93 and IBP-38 were more susceptible than Desireé. The somaclons IBP-27 reached a similar affectation score respect to Solanum chacoense. The rest of the somaclons had an intermediate performance. It was proved the important of using of pathogenic strains of Alternaria solani Sor, for making selection where the natural inoculum source it is weak.